Pengaruh Disiplin Kerja, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kepuasan Kerja dan Kinerja Pegawai - Sri Rahayu; Dahlia Dahlia (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The purpose of this study was to determine the effect of work discipline, work motivation and organizational commitment on employee performance through employee job satisfaction at the Agency for Personnel and Human Resources Development (BKPSDM) Ogan Komering Ulu Regency. This type of research is Explanatory Research with the data used in this study is primary data obtained by using questionnaires and literature study. Data analysis used simple linear regression and multiple regression test with SPSS 26. Meanwhile, hypothesis testing used t test, f test, correlation coefficient, and coefficient of determination. Based on the results of the analysis, it can be concluded that there is a positive and significant influence between work discipline on satisfaction; positive and significant influence between work motivation on satisfaction; positive and significant influence between organizational commitment to satisfaction; positive and significant influence between work discipline, work motivation and organizational commitment to satisfaction; positive and significant influence between work discipline on loyalty; positive and significant influence between work motivation on loyalty; there is a positive and significant effect between organizational commitment to loyalty; there is a positive and significant influence between work discipline, work motivation and organizational commitment to loyalty; and the positive and significant influence between work discipline, work motivation and organizational commitment on employee loyalty through employee job satisfaction.